PENTINGNYA HUMAN RELATIONS DALAM MENINGKATKAN MOTIVASI KERJA PEGAWAI - Mudzhira Nur Amrullah (Jurnal Komodifikasi, 2019)
The purpose of this paper is to illustrate the importance of human relations in motivating employees to work more optimally. Relationships based on the principles of human relations within the organization between leaders and subordinates and between subordinates or employees themselves will encourage the organization to be more productive in achieving its goals perfectly. Therefore many organizations actively seek ways to perfect interpersonal relationships, among their members, because managers or leaders believe that human relation is a very beneficial factor both for the organization itself and for individuals or employees.